Using sightability‐adjusted brood‐pair ratios to estimate waterfowl productivity - Anthony M. Pagano; Courtney L. Amundson; Matthew R. Pieron; Todd W. Arnold; Timothy C. Kimmel (Wildlife Society Bulletin)
ABSTRACT Historically, biologists used brood‐pair ratios (BPRs) as an index to waterfowl productivity to help guide management decisions and evaluate conservation practices. However, BPRs are biased by imperfect detection probabilities, especially for broods. We conducted roadside surveys for breeding waterfowl pairs on 7–8 study sites in the springs of 2006–2008 in northeastern North Dakota, USA. Later each year, we conducted replicate counts of broods on the same wetlands and used mark–recapture methods to estimate sightability‐adjusted BPRs (SA‐BPRs). Traditional roadside brood surveys detected only 30–45% of the available broods, depending on species. We explored the potential for using SA‐BPRs to measure hen success (i.e., the probability a female hatches ≥1 egg across all nesting attempts) for mallards (Anas platyrhynchos) and other upland‐nesting dabbling ducks (Anas spp.). We found that SA‐BPRs explained 40% of the variation in hen success over 5 species of dabbling ducks, and we were able to detect an effect of predator reduction on hen success in combined dabblers, but not in mallards alone. However, we found no relationship between SA‐BPRs and mallard fledging rates (hen success × initial brood size × duckling survival). Our results suggest that SA‐BPRs can provide a cost‐effective alternative to traditional measures of productivity such as nesting success, but not to measures of duckling survival. Nevertheless, SA‐BPRs may be useful in areas where traditional measures of waterfowl productivity are logistically or financially challenging. © 2014 The Wildlife Society.